Analyzing when parental warmth but without parental strictness leads to more adolescent empathy and self-concept: Evidence from Spanish homes - Fuentes, Maria C.; Garcia, Oscar F.; Alcaide, Marta; Garcia-Ros, Rafael; Garcia, Fernando (Frontiers in Psychology, 2022)
Classical research mainly conducted with European-American families has identified the combination of warmth and strictness (authoritative style) as the parenting always associated with the highest scores on developmental outcomes. Additionally, despite the benefits of empathy for prosocial behaviors and protection against antisocial behaviors, most research has considered the contribution of specific practices (e.g., reasoning or power assertion), but not so much the parenting styles. Similarly, family studies tend to study the relationship between parenting and global self-perceptions (self-esteem), but not so much those of each dimension (self-concept). In the present study, 600 Spanish adolescents from 12 to 17 years old (M = 15.25, SD = 2.01) were classified within one of the four household typologies (i.e., authoritative, indulgent, authoritarian, or neglectful). Adolescent developmental outcomes were cognitive empathy (adopting perspectives and emotional understanding), emotional empathy (empathic stress and empathic happiness), and self-concept (academic, social, emotional, family and physical). The results showed that the indulgent parenting (warmth but not strictness) was related to equal or even better empathy and self-concept than the authoritative style (warmth and strictness), whereas non-warm parenting (authoritarian and neglectful) was consistently associated with poor results. Overall, the present findings seriously question that parental strictness combined with parental warmth (authoritative style) is always the parenting style related to the greatest outcomes. By contrast, it seems that reasoning, warmth and involvement, without strictness (indulgent parenting) help adolescents to achieve a good orientation towards others in terms of cognitive and affective empathy and a good self-evaluation in terms of self-concept.